Public Interpretation of Federal Reserve Discount Rate Changes: Evidence on the "Announcement Effect" - Waud, Roger N. (Econometrica, 1970)
[It is often argued that discount rate changes have a "psychological" impact on the public's expectations about the future course of the economy; it is alleged that such changes affect economic activity by influencing the expectations of businesses, financial institutions, and other economic actors. This study attempts to assess the veracity of the notion that there is such an effect of expectations. We begin with the premise that any change in expectations about future net cash accruing to business enterprises really reflects changes in expectations about future economic conditions in general, and that changes in expectations about future cash flows will be reflected in the discounted present value of business firms and hence the market value of equity shares. After removing systematic components from such data, and analysis of the random component strongly suggests that there is an "announcement effect" on expectations associated with discount rate changes, and that there seems to be a consensus as to what the inferred information content of such changes portends for future economic conditions. Also, on days immediately preceding discount rate decreases, there seems to be come evidence of anticipation of the change.]